The 2011 European short sale ban on financial stocks: A cure or a curse? - Luiz Félix; Roman Kräussl; Philip Stork (Goethe University Frankfurt, Center for Financial Studies (CFS), 2013)
Did the August 2011 European short sale bans on financial stocks accomplish their goals? In order to answer this question, we use stock options' implied volatility skews to proxy for investors' risk aversion. We find that on ban announcement day, risk aversion levels rose for all stocks but more so for the banned financial stocks. The banned stocks' volatility skews remained elevated during the ban but dropped for the other unbanned stocks. We show that it is the imposition of the ban itself that led to the increase in risk aversion rather than other causes such as information flow, options trading volumes, or stock specific factors. Substitution effects were minimal, as banned stocks' put trading volumes and put-call ratios declined during the ban. We argue that although the ban succeeded in curbing further selling pressure on financial stocks by redirecting trading activity towards index options, this result came at the cost of increased risk aversion and some degree of market failure.
urn:nbn:de:hebis:30:3-324949
Keywords: G01; G28; 330; short-selling; ban; financial stocks; implied volatility skew; risk aversion